2019
DOI: 10.5334/tohm.489
|View full text |Cite
|
Sign up to set email alerts
|

Injection into the Longus Colli Muscle via the Thyroid Gland

Abstract: BackgroundAnterior forms of cervical dystonia are considered to be the most difficult to treat because of the deep cervical muscles that can be involved.Case ReportWe report the case of a woman with cervical dystonia who presented with anterior sagittal shift, which required injections through the longus colli muscle to obtain a satisfactory outcome. The approach via the thyroid gland was chosen.DiscussionThe longus colli muscle can be injected under electromyography (EMG), computed tomography (CT), ultrasonog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…We are more successful now in pinpointing injections, and in reaching muscles which we could not target earlier [22][23][24][25]. As a case in point, we should mention OCI (obliquus capitis inferior) which plays an essential role in the most frequent form of CD and which used to be only rarely targeted for injection [22,26].…”
Section: Injection and The Use Of Emg And Usmentioning
confidence: 97%
See 2 more Smart Citations
“…We are more successful now in pinpointing injections, and in reaching muscles which we could not target earlier [22][23][24][25]. As a case in point, we should mention OCI (obliquus capitis inferior) which plays an essential role in the most frequent form of CD and which used to be only rarely targeted for injection [22,26].…”
Section: Injection and The Use Of Emg And Usmentioning
confidence: 97%
“…US outlines the anatomical structures more exactly [21], while EMG portrays function better. The two methods are thus not substitutes for one another, but rather complement each other (visibility and function) [5,22].…”
Section: Injection and The Use Of Emg And Usmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound was also proposed as a guidance technique, which allows real-time visualization of the trajectory of an EMG needle, as it is impossible to verify needle positioning in the proper muscle without imaging which may influence treatment outcomes [18]. It has also been reported that the needle traversed the tissue of a thyroid gland without any consequences [16,19]. While on one hand, it may be indeed an attractive addition to guide the procedure, particularly, in a lateral approach to LCo when the needle should be advanced between the anterior scalene muscle and the carotid sheath, which creates a risk of damaging the phrenic nerve, brachial plexus, and even the structures of the carotid sheath, on the other hand, ultrasound guidance demands more human and technical recourses as well as additional costs.…”
Section: Injection Technique and Anatomical Considerationsmentioning
confidence: 99%
“…The injection of the LCo has been regarded as difficult and potentially dangerous [6] and so it is not routinely offered in the clinical setting. There are sporadic case reports [8,9,10] and a short series in the literature describing injection of the longus colli under fluoroscopy [7], CT [8], or ultrasound [9,10] guidance, sometimes under sedation [7]. The majority of descriptions [7,8,9] describe a lateral approach taking the injector close to the carotid sheath.…”
Section: Introductionmentioning
confidence: 99%